Neurosurgery training camp for medical student: experience of the Turkish neurosugery academy and Bursa Uludag University - Unal, H. Setenay; Aydin, Mevlut Okan; Bilgic, Esma; Eser, Pınar; Alper, Zuleyha; Taskapılıoğlu, M. Ozgur; İlker Kafa, M.; Kocaeli, Hasan; Dogan, Seref; Yılmazlar, Selcuk; Bekar, Ahmet; Sekerci, Zeki; et al. (Frontiers in Surgery, 2024)
Introduction: To highlight the importance of hands-on experiences and mentorship in shaping the future workforce of specialized medical professionals via a Neurosurgery Training Camp. Methods: Responses of the questionnaire regarding the Neurosurgery Training Camp organized by Bursa Uludag University's Faculty of Medicine and the Turkish Neurosurgery Academy were reviewed retrospectively. A one-day program was organized to introduce neurosurgery to medical students. During the camp, the students participated in interactive presentations delivered by faculty members, had lunch together, became acquainted with neurosurgical tools and technologies, and performed interventions. With pre and postworkshop questionnaire, student's expectations and thoughts about camp was evaluated.Results: Forty-one students from 10 medical schools, spanning every year of study, attended the camp. Approximately 39% of the attendees (n = 16) were women and 61% (n = 25) were men. The post-workshop survey results demonstrated that 73% of the students (n = 30) were inclined to pursue a career in neurosurgery after the camp, 21.9% (n = 9) remained undecided, and 4.8% (n = 2) chose not to pursue neurosurgery. Feedback from the post-workshop questionnaire highlighted that all students perceived the camp as beneficial in providing insights into their future careers and aiding in making a decision regarding their career paths.The neurosurgical training camp effectively inspired and educated medical students about the discipline of neurosurgery. Furthermore, the camp effectively altered the career aspirations and perceptions of neurosurgery among the participating students.